GENDER REPRESENTATION IN THE MOTIFS AND LITERARY ARTS OF ÈṢÙ - Saadu, Taofiq; Suroyya, Naharin (Martabat: Jurnal Perempuan dan Anak, 2024)
This study probes the representation of gender in the motifs and literary arts of Èṣù, a revered figure in Yorùbá culture. It argues that gender representations in human beings are equally found in Èṣù literary arts. The paper observes that gender representation in Èṣù motifs vis-a-vis its literary arts have semiotic implications in the Yorùbá worldview. It also understudies the interplay between Èṣù motifs and its orature as reflected in human life. The study employs the theoretical framework of the semiotics of Ferdinand de Saussure of 1974 and the gender of Goffman of 1977-1978 to analyze, describe, and interpret the sign portraying gender in Èṣù motifs and literary arts. Through a semiotic analysis, we uncover the symbolic meanings and gendered connotations embedded in Èṣù's iconography and literary depictions. This study reveals that Èṣù's motifs and literary arts perpetuate and challenge traditional gender roles, reflecting the complexities of Yorùbá gender dynamics. By applying Saussure's semiotic theory and Goffman's gender framework, we demonstrate how Èṣù's gender representation influences human gender structure and cultural identity. This study contributes to our understanding of gender representation in African cultural heritage, highlighting the significance of Èṣù's motifs and literary arts as a reflection of human experience.